2001
DOI: 10.1159/000055663
|View full text |Cite
|
Sign up to set email alerts
|

Role of VEGF-A in Endothelial Phenotypic Shift in Human Diabetic Retinopathy and VEGF-A-Induced Retinopathy in Monkeys

Abstract: The endothelium-specific antigen PAL-E, associated with transport vesicles in non-barrier endothelium, is almost absent from barrier capillaries in the normal brain and retina. We have recently demonstrated that only leaking retinal capillaries in diabetic retinopathy (DR) in humans characteristically express PAL-E. Here we investigated the relation between the expression of the PAL-E antigen and vascular endothelial growth factor-A (VEGF) in human post-mortem eyes of individuals with diabetes mellitus (DM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 18 publications
(29 reference statements)
1
31
0
Order By: Relevance
“…36 It is a major player in pathologies involving damage to blood vessels. Using Western blot analysis, we found that protein levels of fibrinogen were significantly higher in retinas of 2-month-old Atm Ϫ/Ϫ mice than in age-matched controls ( Figure 4A).…”
Section: Microhemorrhage Incidents In Atm ϫ/ϫ Micementioning
confidence: 99%
“…36 It is a major player in pathologies involving damage to blood vessels. Using Western blot analysis, we found that protein levels of fibrinogen were significantly higher in retinas of 2-month-old Atm Ϫ/Ϫ mice than in age-matched controls ( Figure 4A).…”
Section: Microhemorrhage Incidents In Atm ϫ/ϫ Micementioning
confidence: 99%
“…It has been reported that changes in Müller cells' function often occurred prior to vascular abnormalities [6][7][8]. These changes include the abnormalities in the a and b waves of electroretinogram (ERG) [9][10][11], altered expression of glial fibrillary acidic protein (GFAP) [12][13][14] and vascular endothelial growth factor (VEGF) [15][16][17][18] in the Müller cells, and always combined with alteration in glutamate metabolism [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…8 Some researches highlighted the role of VEGFinduced damage in ischemic retinopathies 38 and emphasized that overproduction can end up with intensified tissue hypoxia and injury paradoxically. 39 Furthermore, when the milieu is stressed oxidatively, it may activate apoptotic pathways rather than prosurvival routes in endothelial cells. 9,21 It is again reported that VEGF can promote formation of superoxide radicals in cultured retinal endothelial cells.…”
Section: Discussionmentioning
confidence: 99%